An overview of fish stocking in Brazil - Yasmin Martins Pelissoli; Angelo Antonio Agostinho; Marcelo Henrique Schmitz; Fernando Mayer Pelicice (Neotropical Ichthyology, 2023)
Abstract Fish stocking is a common management strategy in Brazil, yet no assessment has examined its real extent and features. The present work investigated fish stocking practices in Brazil between 2010 and 2019 to characterize propagule pressure, species composition, the use of non-native species, geographical and temporal trends, environment types, and responsible agencies. Based on information disseminated on the internet, the study detected 1,155 stocking events (ca. 115 events/year). In total, ca. 56.4 million fish were stocked, with an average of ca. 90 thousand fish/event. We found events in all Brazilian regions involving 436 municipalities and 21 states. Most events occurred in the Northeast region (66.3%), which received alone ca. 41 million fish. Reservoirs were the primary target environment, and the public sector conducted most events. Fish stocking involved 63 taxa, including 14 non-native taxa and three hybrids. Considering the events that informed composition, 62.4% released non-native species, which summed 19.7 million fish. These results provide a broad overview of fish stocking practices in Brazil, and reveal that this action is widely disseminated. Its frequent use, associated with the lack of proper criteria and the illegal stocking of non-native species, raise concerns about technical aspects, outcomes, and potential environmental impacts.